Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 19888728
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use

Antimutagenicity of a suberin extract from Quercus suber cork. - Krizková, L; Lopes, M H; Polónyi, J; Belicová, a; Dobias, J; Ebringer, L (Mutation research, 1999)
The possible protective effect of a suberin extract from Quercus suber cork on acridine orange (AO)-, ofloxacin- and UV radiation-induced mutagenicity (bleaching activity) in Euglena gracilis was examined. To our knowledge, the present results are the first attempt to analyse suberin in relation to mutagenicity of some chemicals. Suberin exhibits a significant dose-dependent protective effect against AO-induced mutagenicity and the concentration of 500 micrograms/ml completely eliminates the Euglena-bleaching activity of AO. The mutagenicity of ofloxacin is also significantly reduced in the presence of suberin (125, 250 and 500 micrograms/ml). However, the moderate protective effect of suberin on UV radiation-induced mutagenicity was observed only at concentrations 500 and 1000 micrograms/ml. Our data shows that suberin extract from Q. suber cork possess antimutagenic properties and can be included in the group of natural antimutagens acting in a desmutagenic manner.
Keywords: Acridine Orange; Acridine Orange: toxicity; Animals; Antimutagenic Agents; Antimutagenic Agents: pharmacology; Euglena gracilis; Euglena gracilis: drug effects; Euglena gracilis: genetics; Euglena gracilis: radiation effects; Lipids; Membrane Lipids; Membrane Lipids: pharmacology; Mutagenicity Tests; Mutagenicity Tests: methods; Mutagens; Mutagens: toxicity; Ofloxacin; Ofloxacin: toxicity; Plant Extracts; Plant Extracts: pharmacology; Plant Shoots; Plant Shoots: chemistry; Spectrophotometry, Ultraviolet; Superoxides; Superoxides: metabolism; Trees; Trees: chemistry; Ultraviolet Rays